2005
DOI: 10.1002/jcb.20612
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein contributions to mammary gland and mammary tumor structure and function: Roles of adherens junctions, ErbBs and membrane MUCs

Abstract: Mammary function is dependent on its three-dimensional organization, which is established and maintained by cell adhesive junctions linked through the membrane to the cell cytoskeleton. These junctions serve not only as structural elements, but also function as initiators and integrators of cell signals. In this review we discuss three types of glycoproteins whose interactions impinge on the function of mammary cell-cell junctions, cadherins, ErbB receptor tyrosine kinases and membrane mucins, as a microcosm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
(58 reference statements)
1
15
0
1
Order By: Relevance
“…It is present in about 90 % of breast cancers; its expression was also significant (p<0.05) in this study. It has been reported that Erbs can bind to the cytoplasmic tail of MUC1 [13]. This relation was also observed in this study since ErbB-2 expression marker was significant (p00.024) [30].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is present in about 90 % of breast cancers; its expression was also significant (p<0.05) in this study. It has been reported that Erbs can bind to the cytoplasmic tail of MUC1 [13]. This relation was also observed in this study since ErbB-2 expression marker was significant (p00.024) [30].…”
Section: Discussionsupporting
confidence: 88%
“…The discovery of the overexpression of ErbB2/HER2/Neu in about 25 % of breast cancers has been focused attention on the ErbB family of receptor tyrosine kinases as a significant contributor to tumor progression. ErbB2 is recognized as an important contributor to some types of breast cancer [13]. Carcinoembryonic antigen (CEA) is a glycoprotein involved in cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that cell-cell junctions, which establish and maintain epithelium three-dimensional organization, are essential to proper MEC function. In fact, these complexes have essential contributions both to tissue structure and to cell signaling since they are structural elements involved in stabilizing the cell layer and providing the permeability barrier between the epithelial lumen and the underlying stroma (Carraway et al, 2005). Thus, the downregulation of FER and FYN observed in Defective CSN1S1 genotype goats suggests a stronger cell-cell interaction that could be linked to MEC function modification (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Among these, β-integrins, 3 MUC-4 4 and CD44 5 are probably the best known candidates whose roles in cancer progression are well documented. 3,6,7 ErbB2 is embedded into this network of signaling and accessory molecules and by its promiscuous association profile it promotes cancer progression. 8 CD44 is recognized as the major hyaluronan receptor having several, alternatively spliced isoforms varying in their physiological function.…”
Section: Introductionmentioning
confidence: 99%